The role of context effects in letter perception - Martišius, V. (Psichologija, 1991)
The study confirms Reicher’s findings that performance on letter identification in words is better than the performance on a single letter. An effect of word facilitation is independent of the number of possible responses. Otherwise the context affects the letter perception in reading task. The subjects made more errors on letter identification in correctly spelled rather than on misspelled words. A letter was perceived worst at all „in contexts with a strongly constraining meaning. Our results are consistent with the principles of an interaction activation model proposed by McClelland and Rumelhart.